Plasma metabolomics identifies signatures that distinguish heart failure with reduced and preserved ejection fraction - Fawaz Naeem; Teresa C. Leone; Christopher Petucci; Clarissa Shoffler; Ravindra C. Kodihalli; Tiffany Hidalgo; Cheryl Tow‐Keogh; Jessica Mancuso; Iphigenia Tzameli; Donald Bennett; John D. Groarke; Rachel J. Roth Flach; et al. (ESC Heart Failure, 2025)
Abstract Aims Two general phenotypes of heart failure (HF) are recognized: HF with reduced ejection fraction (HFrEF) and with preserved EF (HFpEF). To develop phenotype‐specific approaches to treatment, distinguishing biomarkers are needed. The goal of this study was to utilize quantitative metabolomics on a large, diverse population to replicate and extend existing knowledge of the plasma metabolic signatures in human HF. Methods Plasma metabolomics and proteomics was conducted on 787 samples collected by the Penn Medicine BioBank from subjects with HFrEF (n = 219), HFpEF (n = 357) and matched controls (n = 211). A total of 90 metabolites were analysed, comprising 28 amino acids, 8 organic acids and 54 acylcarnitines. Seven hundred thirty‐three of these samples also underwent proteomic profiling via the O‐Link proteomics panel. Results Unsaturated forms of medium‐/long‐chain acylcarnitines were elevated in the HFrEF group. Amino acid derivatives, including 1‐ and 3‐methylhistidine, homocitrulline and symmetric and asymmetric (ADMA) dimethylarginine were elevated in HF, with ADMA elevated uniquely in HFpEF. While the branched‐chain amino acids (BCAAs) were minimally changed, short‐chain acylcarnitine species indicative of BCAA catabolism were elevated in both HF groups. 3‐hydroxybutyrate (3‐HBA) and its metabolite, C4‐OH carnitine, were uniquely elevated in the HFrEF group. Linear regression models demonstrated a significant correlation between plasma 3‐HBA and N‐terminal pro‐brain natriuretic peptide in both forms of HF, stronger in HFrEF. Conclusions These results identify plasma signatures that are shared as well as potentially distinguish HFrEF and HFpEF. Metabolite markers for ketogenic metabolic re‐programming were identified as unique signatures in the HFrEF group, possibly related to increased levels of BNP. Our results set the stage for future studies aimed at assessing selected metabolites as relevant biomarkers to guide HF phenotype‐specific therapeutics.